Probing for missing links in the binary and ternary V(V)-citrate-(H 2O 2) systems: Synthetic efforts and in vitro insulin mimetic activity studies - Gabriel, Catherine; Venetis, J.; Kaliva, Maria; Raptopoulou, Catherine P.; Terzis, Aris; Meier, Beate; Voyiatzis, George A.; Potamitis, Constantinos; Salifoglou, Athanasios; Drouza, Chryssoula (My University, 2009)
In a pH-specific fashion, V 2O 5 and citric acid in the absence and presence of H 2O 2 reacted and afforded, in the presence of NaOH and (CH 6N 3) 2CO 3, two new dinuclear V(V) binary non-peroxo (CH 6N 3) 6[V 2O 4 (C 6H 4O 7) 2] · 2H 2O (1) and ternary peroxo (CH 6N 3) 4[V 2O 2 (Ο 2) 2(C 6H 5O 7) 2] · 6Η 2Ο (2) species, respectively. Complexes 1 and 2 were further characterized by elemental analysis, UV/Vis, FT-IR, NMR (solution and solid state Cross Polarization-Magic Angle Spinning (CP-MAS)) and Raman spectroscopies, cyclic voltammetry, and X-ray crystallography. Both 1 and 2 are members of the family of dinuclear V(V)-citrate species bearing citrate with a distinct coordination mode and degree of deprotonation, with 2 being the missing link in the family of pH-structural variants of the ternary V(V)-peroxo-citrate system. Given that 1 and 2 possess distinct structural features, relevant binary V(III), V(IV) and V(V), and ternary V(V) species bearing O- and N-containing ligands were tested in in vitro cell cultures to assess their cellular toxicity and insulin mimetic capacity. The results project a clear profile for all species tested, earmarking the importance of vanadium oxidation state and its ligand environment in influencing further binary and ternary interactions of vanadium arising with variable mass cellular targets, ultimately leading to a specific (non)toxic phenotype and glucose uptake ability
Keywords: Citric acid; Hydrogen peroxide; Mice; Oxidation; Animals; Biomimetics; Cell lines; Citrates; Crystallography; Hydrogen peroxide; Vanadium picolinate; Cell toxicity; Insulin mimesis; In vitro cell culture tests